Factores de riesgo obstétrico asociados a parto pretérmino en gestantes atendidas en el servicio de gineco-obstetricia del Hospital General Martín Icaza, Babahoyo, mayo – septiembre del 2019 - Mora Alvarado, Grecia Brigitte (2019)
Obstetric risk factors that are associated with preterm birth occur in high rates of perinatal morbidity and mortality, especially in developing countries, becoming a public health problem. This research work, of a retrospective - quantitative type, was carried out with the purpose of determining the obstetric risk factors associated with preterm birth in pregnant patients treated in the gynecology - obstetrics service of the General Martín Icaza Hospital, Babahoyo, May - September from 2019. The analysis of the statistical data showed that the percentage of preterm birth as a result of obstetric risk factors in pregnant patients is 20.5%. Incidence that is maintained in relation to the results compared with other South American developing countries and in publications at regional, national, and international level, for that reason the theoretical proposal proposed is aimed at strengthening prevention and promotion programs that are taught by The Ministry of Public Health, in order to raise awareness among pregnant women and to be able to identify obstetric risk factors to prevent such pathology, by adopting a healthy lifestyle and thus reducing the rates of maternal mortality and morbidity and fetal.